Pelaksanaan Pengawasan UMK Tahun 2017 oleh Disnaker dan ESDM Provinsi Bali (Studi Kasus Upah Dibawah UMK Sektor Pariwisata Kota Denpasar) - Putri, Devi Anggari; Yasintha, Putu Nomy; Wismayanti, Kadek Wiwin Dwi (CITIZEN CHARTER, 2019)
ABSTRACT Implementation of Bali Governor Regulation No. 67 of 2016 concerning 2017’s Minimum Wages must be overseen by the Labor Inspector of the Department of Manpower and Energy Mineral Resources of Bali Province. This research was conducted because implementation minimum wages isn’t optimal, especially tourism sector in Denpasar. This can be seen from number of complaints submitted by workers. The system of implementing supervision is carried out by repressive control in two ways, first by prior notification of business actors to be examined. Second by inspective, examining directly in the company. The conclusion is, implementation control of minimum wages has been implemented well. However, there’re still a number of obstacle, 1) Lack of labor inspectors 2) Low understanding and awareness of companies and employees of regulations 3) Insensitivity to workers reporting violations that occur in the company. The efforts made to overcome these obstacles by 1) Maximizing the potential of Labor Inspectors 2) Conducting socialization to workers and company management 3) Providing guidance to the object of control. Keywords: Control, Minimum Wage, Tourism Sector, Denpasar